A Versatile Nonviral Delivery System for Multiplex Gene‐Editing in the Liver. Issue 46 (14th October 2020) - Gong, Jing; Wang, Hong‐Xia; Lao, Yeh‐Hsing; Hu, Hanze; Vatan, Naazanene; Guo, Jonathan; Ho, Tzu‐Chieh; Huang, Dantong; Li, Mingqiang; Shao, Dan; Leong, Kam W.
Abstract: Recent advances in CRISPR present attractive genome‐editing toolsets for therapeutic strategies at the genetic level. Here, a liposome‐coated mesoporous silica nanoparticle (lipoMSN) is reported as an effective CRISPR delivery system for multiplex gene‐editing in the liver. The MSN provides efficient loading of Cas9 plasmid as well as Cas9 protein/guide RNA ribonucleoprotein complex (RNP), while liposome‐coating offers improved serum stability and enhanced cell uptake. Hypothesizing that loss‐of‐function mutation in the lipid‐metabolism‐related genes pcsk9, apoc3, and angptl3 would improve cardiovascular health by lowering blood cholesterol and triglycerides, the lipoMSN is used to deliver a combination of RNPs targeting these genes. When targeting a single gene, the lipoMSN achieved a 54% gene‐editing efficiency, besting the state‐of‐art Lipofectamine CRISPRMax. For multiplexing, lipoMSN maintained significant gene‐editing at each gene target despite reduced dosage of target‐specific RNP. By delivering combinations of targeting RNPs in the same nanoparticle, synergistic effects on lipid metabolism are observed in vitro and vivo. These effects, such as a 50% decrease in serum cholesterol after 4 weeks of post‐treatment with lipoMSN carrying both pcsk9 and angptl3 ‐targeted RNPs, could not be reached with a single gene‐editing approach. Taken together, this lipoMSN represents a versatile platform for the development of efficient, combinatorial gene‐editing therapeutics. Abstract : A liposome‐coated mesoporous silica nanoparticle enables multiplex gene editing to understand potential therapeutic targets in liver lipid metabolism. Using this novel nonviral platform to deliver CRISPR/Cas9 ribonucleoprotein, gene editing is demonstrated at three potential therapeutic targets ( pcsk9, apoc3, angptl3 ) for cardioprotection in vitro and in vivo.